Some Problems in Stratigraphic Analysis of Fir in Mizuho Plateau, East Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Okitsugu WATANABE; Kikuo KATO; Kazuhide SATOW (National Institute of Polar Research, 1979)
Long-term variation of precipitation and surface temperature in the vicinity of Mizuho Station were studied by means of stratigraphic analyses of 150-m boring core. ln this paper, some problems on snow stratigraphy aroused concerning the analyses are discussed. First, problems on the unit of stratification are discussed in relation to visible stratigraphic elements and deposition-erosion processes Second, phenomena of missing layer corresponding to the hiatus in the layer formation are discussed in relation to regional characteristics of those occurrence and frequency. Precise estimation of mean annual accumulation in a certain perlod may be impossible without quantitative rating of hiatus duration, and establishment of an effective method of rating should be the most important subject for the stratigraphic study. δ^<18>O vertical profiles in snow layer are investigated using the data obtained from high-accumulation area (W46,1958 m a s.l,) in terms of reconsideration of the classical interpretation. As a result, it is found that a part of δ^<18>O oscillation was due to the variation by isotopic discrimination under snow metamorphism